The Influence of Electronic Word of Mouth (e-WOM) and Brand Awareness on Purchase Decision - Maudy Ajeng Sintiya; Noor Aziz; Ardik Praharjo (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2023)
The purpose of this study was to determine the effect of electronic word of mouth and brand awareness on purchasing decisions for Hanasui lipstick products in Malang City. This study uses quantitative research. The population of this study were consumers who had used or bought Hanasui lipstick products in Malang, and the sample was 100 respondents who had bought or used Hanasui lipstick products. Data collection techniques in this study used questionnaires distributed to respondents. The analysis technique used is multiple regression analysis and hypothesis testing using the t-test and F-test, using the SPSS analysis tool. The results of this study indicate that electronic word of mouth has a positive effect on purchasing decisions, brand awareness has a positive effect on purchasing decisions, and electronic word of mouth and brand awareness simultaneously have an effect on purchasing decisions.